IS FINTECH A SUSTAINABLE BUSINESS MODEL FOR THE FUTURE? EMPIRICAL STUDY IN INDONESIA - Suhardjo, Iwan; Meiliana; Tan, Nany; Andreas, Kelvin; Julia (Faculty of Economics and Business University of Mataram, 2024)
The rapid rise of fintech has transformed the financial landscape, presenting both opportunities and challenges. This research assesses the financial performance of fintech companies in Indonesia compared to traditional banks, exploring the influence of sustainability disclosure, market capitalization, and leverage in both fintech and conventional banks. This research applied a quantitative approach using both stakeholder theory and signaling theory. The data used is secondary data from 13 banking companies in Indonesia which is analyzed using panel data regression. Our findings show that fintech banks have a better performance than conventional banks in terms of market capitalization, with the unexpected negative influence of sustainability disclosure on sustainable growth rate. Through a comprehensive analysis of these factors, the research aims to provide valuable insights into the sustainability and prospects of fintech as a key player in Indonesia's evolving financial ecosystem.